A Case of Idiopathic Non-Cirrhotic Portal Hypertension in a Patient With a Left Ventricular Assist Device. (September 2019) - Kothari, Shana; Kalinowski, Michael; Shah, Natasha; Raddawi, Hareth
Idiopathic non-cirrhotic portal hypertension is a rare diagnosis caused by an unknown etiology with elevated intrahepatic portal pressures in the absence of underlying liver disease. We present a unique case of a 57-year-old male with a left ventricular assist device and preserved right ventricular function that was found to have an elevated hepatic venous pressure gradient and sequelae of portal hypertension without underlying liver disease. There is limited treatment available as management is primarily aimed toward preventing complications of the disease. This case highlights the need for further investigative research of this disease entity and its pathogenesis.